No evidence so far of a major role of AKT1 and GSK3B in the pathogenesis of antipsychotic‐induced tardive dyskinesia. (8th January 2019) - Levchenko, Anastasia; Vyalova, Natalya; Pozhidaev, Ivan V.; Boiko, Anastasiia S.; Osmanova, Diana Z.; Fedorenko, Olga Yu.; Semke, Arkadiy V.; Bokhan, Nikolay A.; Wilffert, Bob; Loonen, Anton J.M.; Ivanova, Svetlana A.
Abstract: Objective: AKT1 and GSK3B take part in one of the intracellular cascades activated by the D2 dopamine receptor (DRD2). This receptor is antagonized by antipsychotics and plays a role in the pathogenesis of antipsychotic‐induced tardive dyskinesia (TD). The present study investigated association of several polymorphisms in the two candidate genes, AKT1 and GSK3B, with TD in antipsychotic‐treated patients with schizophrenia. Methods: DNA samples from 449 patients from several Siberian regions (Russia) were genotyped, and the results were analyzed using chi‐squared tests and analyses of variance. Results: Antipsychotic‐induced TD was not associated with either of the tested functional polymorphisms (rs334558, rs1130214, and rs3730358). Conclusions: Despite regulation of AKT1 and GSK3B by DRD2, we found no evidence that these two kinases play a major role in the pathogenesis of antipsychotic‐induced TD. These results agree with previously published data and necessitate further exploration of other pathogenic mechanisms, such as neurotoxicity due to excessive dopamine metabolism.